Do men with prostate cancer and their partners receive the information they need for optimal illness self-management in the immediate post-diagnostic phase? - Janelle V Levesque; Sylvie D Lambert; Afaf Girgis; Jane Turner; Patrick McElduff; Karen Kayser (Elsevier, 2015)
Objective: To (a) determine whether the information provided to men with prostate cancer and their partners in the immediate postdiagnostic phase met their needs; and (b) examine patient and partner satisfaction with the information received. Methods: Pre-intervention survey data from a pilot randomized controlled trial of a self-directed coping skills intervention involving 42 patients with prostate cancer, and their partners were collected to examine their psychosocial concerns/needs. Results: The main concerns for patients and partners were psychosocial in nature such as managing emotions, concern about the future, and losing control. Overall, patients and partners received most information about tests and treatment options. Partners reported receiving significantly less information about support services (P = 0.03) and self-care strategies (P = 0.03) compared to patients. Partners also reported being significantly less satisfied with the information they received (P = 0.007). Conclusions: Whereas medical information is routinely given, patients and partners may benefit from greater information about psychosocial issues arising from cancer. Despite increased recognition of partner's information needs these still remain unmet.